Proteína bruta na dieta do Poecilia reticulata (Peters, 1859), linhagem moscow blue: desempenho produtivo e reprodutivo - Vieira, Auriele Machado (2019)
The present study aimed to evaluate the productive and reproductive performance of guppies (Poecilia reticulata) fed diets containing increasing levels of crude protein. Seven isoenergetic diets were formulated with increasing PB levels (28, 31, 34, 37, 40, 43 and 46%) and offered to random fish groups for 192 days. In the productive performance of the fingerlings, the apparent feed conversion improved significantly (p<0.05) as the PB levels in the diets increased up to 40%. The weight gain improved significantly (p<0.05) up to 37% PB, whereas the diet containing 40% PB gave 100% survival of the fingerlings. In the reproductive performance, females fed the diet containing 43% of protein presented higher (p<0.05) gonadossomatic indexes and gonads weight. While the highest (p<0.05) hepatossomatic indices were observed in the diet with 46% protein. The highest numbers of offspring were obtained by females fed a diet containing 43% PB. In the morphometric variables of the offspring, the best values (p <0.05) were found in females fed with 43% PB. In males, it was observed that those fed with diets containing 34% of PB had the highest (p<0.05) gonadossomatic indices and testis weight. In the hepatossomatic indices, it was observed that there was a significant effect (p<0.05) in the treatment with 43% PB. Based on the results, it is estimated that 40% PB in diet for fingerlings, 43% of PB in a diet for breeding females and 34% of PB in a diet for guppy breeding males of the moscow blue line.